2021
DOI: 10.1007/s00425-021-03692-3
|View full text |Cite
|
Sign up to set email alerts
|

A conserved C-terminal peptide of sorghum phosphoenolpyruvate carboxylase promotes its proteolysis, which is prevented by Glc-6P or the phosphorylation state of the enzyme

Abstract: Main conclusion A synthetic peptide from the C-terminal end of C4-phosphoenolpyruvate carboxylase is implicated in the proteolysis of the enzyme, and Glc-6P or phosphorylation of the enzyme modulate this effect. Abstract Phosphoenolpyruvate carboxylase (PEPC) is a cytosolic, homotetrameric enzyme that performs a variety of functions in plants. Among them, it is primarily responsible for CO2 fixation in the C4 photosynthesis pathway (C4-PEPC). Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Recent studies of Gandullo and colleagues [51] on sorghum leaves found that phosphorylated PEPC is less sensitive to proteolysis than its dephosphorylated form in vivo and in vitro. C 4 -PEPC proteolysis in the presence of pC19 (which is a synthetic peptide containing the last 19 amino acids from the C-terminal end of the PEPC subunit) was prevented by the PEPC allosteric effector glucose 6-phosphate (Glc-6P) and by PEPC phosphorylation [51]. Thus, in such a case, PEPC phosphorylation renders protection from degradation by cathepsin proteases present in semi-purified PEPC fraction (with protease activity) than the dephosphorylated form [51].…”
Section: Posttranslational Modifications (Ptms): Phosphorylation and Monoubiquitination Of Pepcsmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent studies of Gandullo and colleagues [51] on sorghum leaves found that phosphorylated PEPC is less sensitive to proteolysis than its dephosphorylated form in vivo and in vitro. C 4 -PEPC proteolysis in the presence of pC19 (which is a synthetic peptide containing the last 19 amino acids from the C-terminal end of the PEPC subunit) was prevented by the PEPC allosteric effector glucose 6-phosphate (Glc-6P) and by PEPC phosphorylation [51]. Thus, in such a case, PEPC phosphorylation renders protection from degradation by cathepsin proteases present in semi-purified PEPC fraction (with protease activity) than the dephosphorylated form [51].…”
Section: Posttranslational Modifications (Ptms): Phosphorylation and Monoubiquitination Of Pepcsmentioning
confidence: 98%
“…An increase in phosphorylation was a consequence of favorable PPCK1 expression in leaves, while PEPC activity in roots augmented due to the increase in PPC3 expression thus increasing the capacity of sorghum to cope with the ammonium stress [50]. Recent studies of Gandullo and colleagues [51] on sorghum leaves found that phosphorylated PEPC is less sensitive to proteolysis than its dephosphorylated form in vivo and in vitro. C 4 -PEPC proteolysis in the presence of pC19 (which is a synthetic peptide containing the last 19 amino acids from the C-terminal end of the PEPC subunit) was prevented by the PEPC allosteric effector glucose 6-phosphate (Glc-6P) and by PEPC phosphorylation [51].…”
Section: Posttranslational Modifications (Ptms): Phosphorylation and Monoubiquitination Of Pepcsmentioning
confidence: 99%
See 1 more Smart Citation
“…PEPC is phosphorylated by a dedicated Ca 2+ ‐independent Ser/Thr kinase known as PEPC kinase (PPCK) (Echevarría & Vidal, 2003). In addition, sorghum PEPCs may be regulated by other post‐translational modifications (PTMs) such as mono‐ubiquitination (Ruiz‐Ballesta et al., 2014), S ‐nitrosylation, and carbonylation (Baena et al., 2017) or binding to anionic phospholipids (Gandullo et al., 2019; Monreal et al., 2010), altering the exposition of its C‐terminal end (Gandullo et al., 2021), modulating even further its activity and/or stability and adding more complexity to the study of PEPC regulation in vivo .…”
Section: Introductionmentioning
confidence: 99%